Claim Category in Indonesian Coffee Discourse Argument - Rusdhianti Wuryaningrum; Ahmad Syukron; Arju Muti'ah (JURNAL ARBITRER, 2022)
The objective of this research is to describe the construction of claims in the strategies used in the coffee discourse. The claim in the argument can show cognition about coffee that is implanted by the producer. his research takes data from the online discourse of Indonesian coffee. The data of this research are statements that are contextually interpreted as claims and then examined from the Toulmin concept. By studying the types of claims, types of claims and its strategy to connect claims and ground, the researcher describes the arguments in the coffee discourse. From the results of the qualitative study, it is obtained that there are three types of claims, namely fact-based claims, judgment and value claims, and claim-based policies. From the three types of claims it can be concluded that there are. From the results and discussion it can be stated that there are subjective and objective claims formed in the coffee discourse. Objective claims are proven by geographical location, research, knowledge and environmental conservation in industrial agriculture (future knowledge). Subjective claims are shown by personality and support quality. Regarding history, as an aspect of judgment and value claims, it is subjective and objective. From these claims, it can be seen that the coffee discourse contains cognitions about coffee companies with historical authority, personality, and taste; future knowledge and research references; taste, packaging, and good process.